Immigration and Crime Taking Stock - Kubrin, Charis E.; Ousey, Graham C. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This brief examines various dimensions of the immigration-crime relationship in the United States. It evaluates a range of theories and arguments asserting an immigration-crime link, reviews studies examining its nature and predictors, and considers the impacts of immigration policy. Synthesizing a diverse body of scholarship across many disciplinary fields, this brief is a comprehensive resource for researchers engaged in questions of linkages between crime and immigration, citizenship, and race/ethnicity, and for those seeking to separate fact from fiction on an issue of great scientific and social importance.
Chapter 1: Introduction -- Chapter 2: Studying Immigration and Crime: A Precursory Note -- Chapter 3: Theoretical Perspectives on Immigration and Crime -- Chapter 4: From Theory to Empirics: Data Requirements for Studying Immigration and Crime -- Chapter 5: Immigration and Crime: What do We Know? -- Chapter 6: Immigration and Crime: What don't We Know? -- Chapter 7: Undocumented Immigration -- Chapter 8: The Devolution of Immigration Enforcement: Do Immigration Policies and Practices Matter? -- Chapter 9: Conclusion.
Keywords: Criminology; Crime -- Sociological aspects; Community psychology; Criminology; Crime and Society; Community Psychology